Comparative Transcriptome Analysis Between a Spontaneous Albino Mutant and Its Sibling Strain of Cordyceps militaris in Response to Light Stress - Wang, Fen; Liu, Qing; Zhang, Jiaojiao; Liu, Kuanbo; Li, Kuan; Liu, Guijun; Dong, Caihong (Frontiers in Microbiology, 2018)
Albinism has been used for new variety screening in some edible mushrooms and the underlying mechanisms are fascinating. Albino fruiting body of Cordyceps militaris, a well-known edible fungus and model organism for Cordyceps, has the potential for nutraceuticals or functional foods due to its high content metabolites and antioxidant activities. In this study, a spontaneous albino mutant strain (505) of C. militaris was obtained. Comparing with its normal sibling strain (498), albino strain remained white stably in response to light and decreased conidia and carotenoid production significantly but accumulated more cordycepin. Transcriptome analysis revealed that all the seven photoreceptors had the same expression pattern in response to light between the two strains. However, many more genes in the albino strain were differentially expressed in response to light than its sibling strain. The significantly enriched pathways in 498L vs 505L were mainly associated with replication and repair. Some secondary metabolites backbone genes including encoding DMAT, two NRPS-like proteins, three NPRS, and lanosterol synthase were differentially expressed in the albino compared with the normal strains. Transcriptome and real-time quantitative PCR analysis indicated some cytochrome P450s and methyltransferases might also related with the phenotype difference of the two strains. This study compared the genome-wide transcriptional responses to light irradiation between a spontaneous albino mutant and its normal sibling strain of an edible fungus and paves the way for further investigation of the pigment biosynthetic pathway.